Perancangan Dan Simulasi Antena Fleksibel Menggunakan Substrat Polydimethylsiloxane Untuk Aplikasi Pendeteksi Tumor Payudara - Hilmi, Muhammad Fadhlurrahman; Rahayu, Yusnita; Wahyu, Yuyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Microwave imaging system is one of the technologies that can be used to detect objects, especially in the field of medical diagnoses, such as detecting tumors in the breast. The technology used is ultrawideband (UWB) with the advantages of low cost, low power consumption, and high transmission capacity. In this study, a flexible antenna was designed at a frequency of 5.8 GHz using a polydimethylsiloxane (PDMS) substrate with a dielectric constant of 2.67 – 3.00 and a loss tangent of 0.02-0.05 for breast tumor detection applications. The antenna design process uses the CST studio suite software. The simulation results of a flexible antenna at an operating frequency of 5.8 GHz with a return loss parameter of -39.19 dB, a VSWR of 1.22, a bandwidth of 3.1 GHz in a frequency range of 4.52–7.62 GHz, the resulting radiation pattern is almost omnidirectional, and a gain of 2.26 dBi. In addition, the gain of flexible antenna with phantom breast without tumor is -23.62 dB and phantom breast with tumor is -24.85 dB at operating frequency of 5.5 GHz, which is shifted by 300 MHz from the desired frequency. Keywords: microwave, ultra-wideband (UWB), flexible antenna, polydimethylsiloxane (PDMS)